Prevalence of foot problems associated with wearing safety footwear in factory employees - Dumbhare, Shruti A.; Nagarwala, Raziya M.; Shyam, Ashok K.; Sancheti, Parag K. (International Journal Of Community Medicine And Public Health, 2022)
Background: In majority of heavy industries and factories safety footwear is a mandatory safety obligation, thus a necessity for workers in industrial settings, contributing to foot problems, interfering with work capacity. Therefore, there is an urgent need to find prevalence of foot problems occurring due to safety footwear. To find the prevalence of foot problem associated with wearing safety footwear in factory employees. Methods: Factory employees working in industrial setting wearing safety footwear for prolonged duration on regular basis were included in the study. Subjects having any recent ankle and below knee fractures in last 6 months were excluded. Samples were collected from different industrial settings, with the help of a self-made questionnaire. Descriptive analysis of the data collected was done and the responses were converted into percentiles and represented in graphical form. Results: 62.50% subjects complain pain in the heel and bottom of the foot (plantar fasciitis), 50.83% pain in the foot (radiating up to calf), 47.50% excessive heat/wet condition, 30.83% hard dead skin on the pressure areas of the foot (foot corn), 12.50% blisters/swelling on the foot, bump/bulge on the joint at the base of the big toe (bunion), numbness of great toe, 10.83% interference with blood circulation. 43.34% employees the intensity of pain caused by wearing safety footwear interfere with their working capacity. For 43.34% employees the intensity of pain caused by wearing safety footwear interferes with their working capacity. Conclusions: It can be concluded that there is significant prevalence of foot problems caused due to wearing safety footwear. These foot problems limit the working capacity of the individual.